The development of Australian abortion laws in a worldwide trend, free and legal practices of abortion and a glance at abortion laws in Iran - SH Hosseini (JRI, 2005)
The study of historical development of criminal law in different countries shows that abortion has initially been regarded as a crime with severe punishment in many countries, including Australia. Abortion is an inevitable universal phenomenon, and according to statistics released in 1990, the worldwide number of attempts for abortion was estimated to be between 36 to 50 million a year, which only one third of them were carried out legally and with access to modern clinical and pharmaceutical facilities. On the basis of statistics provided by World Health Orga-nization (WHO) in 1990, around 61000 pregnant mothers lose their lives every year due to un-safe abortions. The high percentage of maternal mortalities, particularly in the third world count-ries, was scrutinized and recognized as a big concern in the Population and Development Confe-rence held in Cairo in 1994. Consequences and difficulties due to the absolute prohibition of abortion, promoted the legislative and executive bodies of many countries to more realistically allow legal abortions under particular circumstances while, still no realistic changeovers have been accorded in laws of abortion in some other countries, including Iran, and accordingly, people in these countries are suffering from the absolute prohibition of abortion. Upon review-ing the development of abortion laws in Australia, this article studies the logical flexibility of some countries over the social phenomenon of abortion and relevant reforms of laws in those countries. By analyzing the social and jurisprudential bases and resources of law, the article also reaches to a conclusion that necessitates law reform, and allows practice of legal abortion under defined circumstances in Iran.
Keywords: Abortion, Law, Reform, Prohibition, Australia, Iran